Folic acid supplementation during early hepatocarcinogenesis: cellular and molecular effects - Andrade Chagas, Carlos Eduardo; Bassoli, Bruna Kempfer; Soares de Souza, Camila Alexandre; Deminice, Rafael; Jordao Junior, Alceu Afonso; Paiva, Sergio Alberto Rupp de [UNESP]; Zaidan Dagli, Maria Lucia; Ong, Thomas Prates; Moreno, Fernando Salvador (Wiley-Blackwell, 2011)
Folic acid (FA) supplementation during carcinogenesis is controversial. Considering the impact of liver cancer as a public health problem and mandatory FA fortification in several countries, the role of FA supplementation in hepatocarcinogenesis should be elucidated. We evaluated FA supplementation during early hepatocarcinogenesis. Rats received daily 0.08 mg (FA8 group) or 0.16 mg (FA16 group) of FA/100 g body weight or water (CO group, controls). After a 2-week treatment, animals were subjected to the "resistant hepatocyte" model of hepatocarcinogenesis (initiation with diethylnitrosamine, selection/promotion with 2-acetylaminofluorene and partial hepatectomy) and euthanized after 8 weeks of treatment. Compared to the CO group, the FA16 group presented: reduced (p < 0.05) number of persistent and increased (p < 0.05) number of remodeling glutathione S-transferase (GST-P) positive preneoplastic lesions (PNL); reduced (p < 0.05) cell proliferation in persistent GST-P positive PNL; decreased (p < 0.05) hepatic DNA damage; and a tendency (p < 0.10) for decreased c-myc expression in microdissected PNL. Regarding all these parameters, no differences (p > 0.05) were observed between CO and FA8 groups. FA-treated groups presented increased hepatic levels of S-adenosylmethionine but only FA16 group presented increased S-adenosylmethionine/S-adenosylhomocysteine ratio. No differences (p > 0.05) were observed between experimental groups regarding apoptosis in persistent and remodeling GST-P positive PNL, and global DNA methylation pattern in microdissected PNL. Altogether, the FA16 group, but not the FA8 group, presented chemopreventive activity. Reversion of PNL phenotype and inhibition of DNA damage and of c-myc expression represent relevant FA cellular and molecular effects.
Keywords: folic acid supplementation; hepatocarcinogenesis; chemoprevention; preneoplastic lesions